2021
DOI: 10.1186/s13017-021-00364-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the COVID pandemic lockdown measures on surgical emergencies: experience and lessons learned from a Greek tertiary hospital

Abstract: Background The COVID-19 pandemic caused a rise in healthcare demands leading to significant restructuring of hospital emergency departments worldwide. The aim of the present study is twofold: firstly, to discern any differences in regard to reason for surgical emergency department (SED) attendance and hospital admission during the pandemic and pre-pandemic eras in Greece, and secondly, to assess the impact of the lockdown measures implemented during the pandemic on SED patient attendance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 13 publications
(12 reference statements)
3
7
0
7
Order By: Relevance
“…[26,27]. In addition, the reduction in the number of emergency hernia repair surgeries reported is in line with previous studies [28]. We must point out that we compared the percentages within the two time periods of the emergency surgeries performed.…”
Section: Discussionsupporting
confidence: 86%
“…[26,27]. In addition, the reduction in the number of emergency hernia repair surgeries reported is in line with previous studies [28]. We must point out that we compared the percentages within the two time periods of the emergency surgeries performed.…”
Section: Discussionsupporting
confidence: 86%
“…A limitation of any national administrative dataset is that hospital coding systems may not function optimally during a pandemic due to staff redeployment. Nonetheless, the 20% reduction identified in Ireland is remarkably consistent with observations from other health systems making this less likely [10,12]. There are gaps in our understanding of the fate of individuals considered for, but not ultimately undergoing, emergency surgery.…”
Section: Discussionsupporting
confidence: 71%
“…Reichert et al surveyed 98 collaborators from thirty-one countries with 87% of respondents reporting a decrease in the number of patients undergoing emergency surgery [11]. Reasons for this reduction in EAS could include patients avoiding healthcare facilities due to the risk of hospital-acquired SARS-CoV-2 infection [10,12,13], people being encouraged to stay at home [9,13], GPs favouring conservative measures instead of referring patients to ED [10,12], and possibly a more refined understanding of what constitutes a surgical 'emergency'. It is noteworthy that reductions happened during both waves, making it less likely that fear of the initially unknown impact of SARS-CoV-2 infection on surgical outcomes [22] or shortages of personal protective equipment were key factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orthopaedic trauma consultations and admissions were not the only service that decreased during the pandemic. 41 The provision of other services, such as emergency room visits 42 and neurosurgical procedures 43 also decreased. One study revealed a 63.3% reduction in operative volume among general surgery patients.…”
Section: Discussionmentioning
confidence: 99%